Review of the genus Suwallia (Plecoptera: Chloroperlidae) from China with description of Suwallia jihuae sp. nov. from Sichuan Province - Chen, Zhi-Teng (Zootaxa, 2019)
A new species of the chloroperlid genus Suwallia Ricker, 1943, S. jihuae sp. nov. from Sichuan Province of southwestern China is described, illustrated and compared with similar taxa. The male of the new species is distinguished from other known Chinese Suwallia species by the H-shaped sclerite on tergum 10. The distribution and taxonomy of the males of the five-known species of Suwallia from China are reviewed. A key to the adult males known from China is provided.